Definition and Risks of Cytokine Release Syndrome in 11 Critically Ill COVID-19 Patients With Pneumonia: Analysis of Disease Characteristics. (30th June 2020) - Wang, Wenjun; Liu, Xiaoqing; Wu, Sipei; Chen, Sibei; Li, Yimin; Nong, Lingbo; Lie, Puyi; Huang, Liyan; Cheng, Linling; Lin, Yongping; He, Jianxing
Abstract: Corona virus disease 2019 (COVID-19) patients with severe immune abnormalities are at risk of cytokine release syndrome (CRS). The definition, prevention, and treatment of symptoms of CRS in critically ill patients with COVID-19 are important problems. We report a single-center case series of 11 COVID-19 patients with acute respiratory distress syndrome from The First Affiliated Hospital of Guangzhou Medical University in China from 26 January 2020 to 18 February 2020. The termination date of follow-up was 19 February 2020. Eight patients were determined to have characteristics of CRS, including pulmonary inflammation, fever, and dysfunction of nonpulmonary organs. An increase in interleukin-6 in peripheral blood was the highest risk factor and an early indicator of CRS in COVID-19. Abstract : IL-6 was the highest risk factor and an early indicator of cytokine release syndrome in COVID-19.